2023
DOI: 10.2196/45216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Peer-Support Mobile App for Mental Health and Substance Use Among Adolescents Over 12 Months During the COVID-19 Pandemic: Randomized Controlled Trial

Abstract: Background Although it is well known that adolescents frequently turn to their friends for support around mental health and substance use problems, there are currently no evidence-based digital programs to support them to do this. Objective The aim of this study was to evaluate the efficacy of the Mind your Mate program, a digital peer-support program, in improving mental health symptoms, reducing the uptake of substance use, and increasing help seeking… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previous studies have rarely investigated the experiences, attitudes, or perceptions of AYAs regarding DMHIs as a main focus [32,33]. Lots of research often collected participants' feedback after evaluating a particular DMHI [17,33]. Consequently, the present findings on the facilitators or barriers of DMHI utilisation are predominantly indirect and fragmented and necessitate a cohesive and logical integration of information about the factors that hinder and promote the use of DMHIs.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Previous studies have rarely investigated the experiences, attitudes, or perceptions of AYAs regarding DMHIs as a main focus [32,33]. Lots of research often collected participants' feedback after evaluating a particular DMHI [17,33]. Consequently, the present findings on the facilitators or barriers of DMHI utilisation are predominantly indirect and fragmented and necessitate a cohesive and logical integration of information about the factors that hinder and promote the use of DMHIs.…”
Section: Introductionmentioning
confidence: 91%
“…A total of 19 studies contained a conflict-of-interest component, of which seven [5,8,10,16,17,41,42] declared a potential or actual conflict of interest. Via quality assessment (Table 2), it was found that the quality of qualitative studies and quantitative randomised controlled trial studies was generally good, while all quantitative descriptive studies vary in degrees of sample representativeness.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations